USING A SPELLING DICTIONARY IN STUDYING LITERACY AND CORRECTING STUDENTS’ MISTAKES - Akhmadjonova Makhfuza Egamkulovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article is based on the fact that error correction methods that require more independent work can also be used. Underlining the error without correcting it, underlining the misspelled letter or the syllable or word containing this letter are also methods of error correction. But these methods should not be mixed in debugging. The age of the students, the simplicity or complexity of the rules, the level of assimilation to the students and their independent work should be taken into account.